Transitions in Vocational Education - Seifried, Jürgen; Wuttke, Eveline (Research in Vocational Education, 2013)
This volume focuses on the different passages and transitions in Vocational Education and professional work life. Exploring the personal experiences of coping with the transition from school to vocational education, vocational education to work, and - finally - within work life, the book takes account of the rapidly changing conditions under which these processes take place